Design, construction, and test of compact, distributed-charge, X-band accelerator systems that enable image-guided, VHEE FLASH radiotherapy - Barty, Christopher P. J.; Algots, J. Martin; Amador, Alexander J.; Barty, James C. R.; Betts, Shawn M.; Castañeda, Marcelo A.; Chu, Matthew M.; Daley, Michael E.; De Luna Lopez, Ricardo A.; Diviak, Derek A.; Effarah, Haytham H.; Feliciano, Roberto; et al. (Frontiers in Physics, 2024)
The design and optimization of laser-Compton x-ray systems based on compact distributed charge accelerator structures can enable micron-scale imaging of disease and the concomitant production of beams of Very High Energy Electrons (VHEEs) capable of producing FLASH-relevant dose rates (∼ 10 Gy in less than 100 ns). The physics of laser-Compton x-ray scattering ensures that the x-rays produced by this process follow exactly the trajectory of the electrons from which the x-rays were produced, thus providing a route to not only compact VHEE radiotherapy but also image-guided, VHEE FLASH radiotherapy. This manuscript will review the compact accelerator architecture considerations that simultaneously optimize the production of laser-Compton x-rays from the collision of energetic laser pulses with high energy electrons and the production of high-bunch-charge VHEEs. The primary keys to this optimization are use of X-band RF accelerator structures which have been demonstrated to operate with over 100 MeV/m acceleration gradients. The operation of these structures in a distributed charge mode in which each radiofrequency (RF) cycle of the drive RF pulse is filled with a low-charge, high-brightness electron bunch is enabled by the illumination of a high-brightness photogun with a train of UV laser pulses synchronized to the frequency of the underlying accelerator system. The UV pulse trains are created by a patented pulse synthesis approach which utilizes the RF clock of the accelerator to phase and amplitude modulate a narrow band continuous wave (CW) seed laser. In this way it is possible to produce up to 10 µA of average beam current from the accelerator. Such high current from a compact accelerator enables production of sufficient x rays via laser-Compton scattering for clinical imaging and does so from a machine of “clinical” footprint. At the same time, the production of 1,000 or greater individual micro-bunches per RF pulse enables > 10 nC of charge to be produced in a macrobunch of < 100 ns. The design, construction, and test of the 100-MeV class prototype system in Irvine, CA is also presented.